A comparison of equity carve-outs and seasoned equity offerings - Schipper, Katherine; Smith, Abbie (Journal of Financial Economics, 1986)
This paper investigates share price reactions of parent firms to announcements of public offerings of stock of wholly-owned subsidiaries. The average abnormal gains associated with ‘equity carve-out’ announcements contrast with the average abnormal losses documented here and elsewhere upon announcements of public offerings of parent equity. Four features distinguishing equity carve-outs from parent equity offerings are discussed. Evidence is provided on these features as potential explanations for the positive average share price reaction associated with announcements of equity carve-outs.